2022
DOI: 10.1021/jacs.2c02165
|View full text |Cite
|
Sign up to set email alerts
|

Designing Protease-Triggered Protein Cages

Abstract: Proteins that self-assemble into enclosed polyhedral cages, both naturally and by design, are garnering attention for their prospective utility in the fields of medicine and biotechnology. Notably, their potential for encapsulation and surface display are attractive for experiments that require protection and targeted delivery of cargo. The ability to control their opening or disassembly would greatly advance the development of protein nanocages into widespread molecular tools. Toward the development of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Previous studies reported that a metal-chelator, reducing agent, or protease can trigger protein disassembly as external stimuli. [63][64][65] Similarly, we explored whether such changes could regulate the heteroassembly. The addition of 13 mM citrate (26% v/v) prior to or during dCA/KDGA assembly in TAPS buffer signicantly perturbed the PPI formation (Fig.…”
Section: Self-assembly Of Dimeric Ca and Kdga Enzymesmentioning
confidence: 99%
“…Previous studies reported that a metal-chelator, reducing agent, or protease can trigger protein disassembly as external stimuli. [63][64][65] Similarly, we explored whether such changes could regulate the heteroassembly. The addition of 13 mM citrate (26% v/v) prior to or during dCA/KDGA assembly in TAPS buffer signicantly perturbed the PPI formation (Fig.…”
Section: Self-assembly Of Dimeric Ca and Kdga Enzymesmentioning
confidence: 99%
“…Reprinted with permission from ref. [ 52 ]; Copyright 2022, American Chemical Society. c Schematic illustration of formation of ferritin cage-based activatable probes.…”
Section: Supramolecular Approaches In Biosensingmentioning
confidence: 99%
“…The Yeates group introduced protease-cleavable sequences into proteins designed to form protein cages through self-assembly, which allowed the nanostructures to disassemble responding to the specific enzymes (Fig. 3 b) [ 52 ]. Depending on the type of introduced sequence, the protein cages exhibited selective changes in the supramolecular structure under conditions associated with diseases, such as cancer, Alzheimer’s disease, and blood coagulation.…”
Section: Supramolecular Approaches In Biosensingmentioning
confidence: 99%
“…They exhibit favorable properties and possess promising potential for applications in the fields of supramolecular chemistry and porous materials. [20][21][22][23][24][25][26] The homogeneity of porous molecular cages enables their use in solution-based processing and mechanistic studies, where they can preorganize substrates, stabilize reactive intermediates, and increase local concentrations. As a result, these cages have found widespread application in enzyme-mimicking catalysis.…”
Section: Introductionmentioning
confidence: 99%